2003
DOI: 10.1590/s1516-35982003000100016
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo e desempenho de coelhos alimentados com rações contendo milheto (Pennisetum glaucum (L.) R.Br)

Abstract: RESUMOABSTRACT -Three experiments were carried out to determine the nutritive value and to evaluate the performance of growing rabbits on fed isoenergy rations containing different pearl millet levels. In a digestibility assay (experiment 1) the nutritive values of Common, BN2 and Iapar IA 98301 pearl millet were determined for 40 male New Zealand White rabbits, 45 days old, allotted in a completely randomized design, with 10 replications. Pearl millet replaced 30% of reference ration in each treatment. Values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
4
2
0
2
Order By: Relevance
“…Similar values of crude protein digestibility coefficient of pearl millet were found by Fialho et al (1999) and Pinheiro et al (2003): 86.20 and 86.25%, on a DM basis, respectively. The values observed by Furlan et al (2003) were 75.86, 87.65 and 83.51% crude protein digestibility coefficient, also close to the ones found in this experiment.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar values of crude protein digestibility coefficient of pearl millet were found by Fialho et al (1999) and Pinheiro et al (2003): 86.20 and 86.25%, on a DM basis, respectively. The values observed by Furlan et al (2003) were 75.86, 87.65 and 83.51% crude protein digestibility coefficient, also close to the ones found in this experiment.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained by Furlan et al (2003), who found the coefficient of dry matter digestibility of 85.62; 88.26 and 88.14% for common pearl millet, BN2 and IAPAR, respectively, also for rabbits. However, Lawrence et al (1995) Table 4 -Coefficient of digestibility and digestible nutrients of pearl millet ADR 7010, based on total dry matter pearl millet and for common pearl millet, respectively, which are values lower than the ones found in this experiment (Table 4).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations